"Do We Have to Call It That?" The Response of Neoliberal Multiculturalism to College Antiracism Efforts. (2nd October 2017) - Case, Alissa; Ngo, Bic
Abstract : The authors discuss the ways in which neoliberal multiculturalism influences the reception and implementation of antiracist initiatives on college campuses. They suggest the intersections of neoliberalism and racism produce a resistance to antiracist efforts and desire for softened multicultural approaches that maintain the status quo. Since the logics of White supremacy and capitalism dominate every space of our society, critical multiculturalism must address these oppressive systems in antiracism education.